Study of the social-demographic and psychosocial profile of mothers of newborns and their knowledge about Newborn Hearing Screening - Fernanda Donato Mahl; Ângela Leusin Mattiazzi; Otília Valéria Melchiors Angst; Themis Maria Kessler; Eliara Pinto Vieira Biaggio (O Mundo da Saúde)
This study aimed to characterize the social-demographic and psychosocial profiles of mothers of newborns submitted to Newborn Hearing Screening (NHS); to evaluate their knowledge of NHS and to measure the level of maternal anxiety towards baby testing. Subjects were 107 mothers who at the outset answered a questionnaire in order to supply socioeconomic (education and occupation), demographic (age and marital status) and psychosocial (social support and planning of pregnancy) data. The second part of the questionnaire referred to aspects of the NHS: the importance and the knowledge about NHS, procedures’ informant, consequences of the hearing loss and the feelings involved in making NHS. Then, to investigate the level of maternal anxiety prior to NHS, an anxiety questionnaire was used. The mothers’ ages ranged from 14 to 44 years, 53.27% of the women have educational status equal or inferior to Elementary School. As regards occupation, 66.36% of the interviewed mothers said to be housewives, 64.49% of them are married and 88.78% of them planned pregnancy. When investigating the social support, 88.79% of them have a husband as financial, affective and emotional support. As regards knowledge about NHS, 76.64% did not know what it was. In addition, 42% of the mothers knew that their children were submitted to the procedure during hospitalization and the nurse was the main health professional who informed them about NHS. It was observed that negative reactions (81.70%) about NHS predominated when mothers did not know what the procedure is. It was concluded that the profile was: mothers are young, have low education, the majority is housewives, married, having social support from the husband and planned pregnancy. Knowledge of NHS was rare. There was a relationship between negative feelings about the test and the lack of knowledge about NHS.